2010
DOI: 10.1155/2010/678360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticides on the Growth and Reproduction of Earthworm: A Review

Abstract: Scientific literature addressing the influence of pesticides on the growth and reproduction of earthworm is reviewed. Earthworms are considered as important bioindicators of chemical toxicity in the soil ecosystem. Studies on this aspect are important because earthworms are the common prey of many terrestrial vertebrate species such as birds and small mammals, and thus they play a key role in the biomagnification process of several soil pollutants. Majority of the studies have used mortality as an endpoint rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(60 citation statements)
references
References 55 publications
(78 reference statements)
1
48
0
3
Order By: Relevance
“…Other research also showed that malathion exposure gave the significant reduction in body weight and decreased sperm viability of Eisenia fetida adults species. The organism also had an adverse impact on growth and reproduction by the chlorpyrifos exposure, and the cypermethrin exposure also gave the significant reduction in cocoon production [3][4][5][6]. Pesticides which are applied to the soil could have an impact on nontarget organisms and damage the local metabolism that is required by soil fertility and pesticide degradation itself [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other research also showed that malathion exposure gave the significant reduction in body weight and decreased sperm viability of Eisenia fetida adults species. The organism also had an adverse impact on growth and reproduction by the chlorpyrifos exposure, and the cypermethrin exposure also gave the significant reduction in cocoon production [3][4][5][6]. Pesticides which are applied to the soil could have an impact on nontarget organisms and damage the local metabolism that is required by soil fertility and pesticide degradation itself [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in VRG, the presence of manure, along with the lack of agrochemicals which can inhibit the micro-and macro-organisms in the soil and the manure (Hussain et al, 2009;Yasmin and D'Souza, 2010), suggest that the flow of SOM is more dynamic in VRG than NT systems, which receive an annual application of herbicides and insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Lima et al (2010) encontraron un aumento en los efectos deletéreos del carbaril sobre la lombriz de tierra Eisenia andrei Bouché, 1972 (Oligochaeta). Yasmin & D'Souza (2010) han encontrado efectos en la reproducción de Eisenia fetida (Savigny, 1826). En contraste al presente estudio que mostró alta toxicidad del carbaril a diferentes entomófagos del control biológico; en las larvas y en las obreras del polinizador Apis mellifera Linnaeus, 1758 se ha observado un bajo riesgo por acción del carbaril (Sánchez-Bayo & Goka, 2014).…”
Section: Aspectos éTicosunclassified